Participation in Medical Tourism versus Physical Activity of Patients after Liposuction: What are the Concerns about Health and Quality of Life? - Lubowiecki-Vikuk Adrian (Sciendo, 2016)
Nowadays, the act of taking care of one's appearance has become a marker of a healthy lifestyle among both women and (mostly metrosexual) men. Physical activity plays a minor role, and tourist trips are more and more frequently combined with the consumption of medical services, including surgery and aesthetic dermatology. The aim of this study is to explain the phenomenon of medical tourism, particularly the specialized category of medical tourism for liposuction treatments, and its relation to the values of physical culture. The work is theoretical; it is supplemented by references to the presented issues in the form of a case study of "lipotourism" and its participants. As a result, the profile of a medical tourist has been identified against which a "lipotourist" constitutes an inimitable case. It seems that although the purpose for the travels of such a tourist is recognized, it still remains a matter of conjecture in terms of experience and behavior.